The development of HOTS-based assessment instruments on educational statistics - Siti Sarah; Dian Aswita; Nur Ainun; Maulidar Maulidar; Muhammad Azzarkasyi (International Journal of Trends in Mathematics Education Research, 2022)
The 21st century demanded that humans have various life skills. HOTS (High Order Thinking Skills) was a competency that leads to the formation of various 21st century life skills. Achieving HOTS on educational process was the basis. This study aimed to produce a HOTS-based assess-ment instrument in educational statistics that was valid and reliable. This research and develop-ment consisted of 8 steps, namely (1) determining the specifications of the instrument, (2) writing the instrument, (3) making a measurement scale, (4) selecting a rating system, (5) reviewing the instrument, (6) testing the instrument, (7) analyze the instrument, (8) compose the instrument. The research subjects were students of Tarbiyah and Teacher Training Faculty, State Islamic Universi-ty Professor K.H. Saifuddin Zuhri in the fourth and sixth semesters as many as 194 people for the 2020-2021 academic years. Data collected by tests. Data analyzed was in the form of validation (content and construct) and reliability tests. The research produced a valid and reliable HOTS-based test as many as 32 items with Cronbach’s Alpha of 0.658 in the high category.